EFFECTIVENESS OF MARINE FUNGI AS FEED ADDITIVE ON NATIVE CHICKEN PERFORMANCE - Nurhayati, Nurhayati; Nelwida , Nelwida; Lisna, Lisna; Ramadan , Fauzan; Tarman, Kustiariyah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to determine the effectiveness of marine fungi as a feed additive on the performance of native chickens. One hundred and eighty unsex one-day-old native chickens were used in this study. Chickens were kept for ten weeks and given a treatment supplemented with the dietary marine fungi (1, 2, 3, and 4 ml/kg) in a ration consisting of yellow corn, rice bran, fish meal, soybean meal, coconut meal, L-lysine, methionine, and CaCO3. The data collected were feed consumption, body weight gain, carcass percentage, mortality rate, and feed efficiency. The results showed significant (P<0.05) decreased feed consumption and increased mortality with adding marine fungi. They did not affect the body weight, carcass percentage, and feed efficiency. The highest mortality occurred in a group of chickens supplemented with marine fungi as much as 3 ml/kg. It was concluded that marine fungi could be added to the ration as much as 1 ml/kg from the beginning of keeping to improve the performance of native chickens effectively and increase the chicken’s immunity. It is suggested to mix marine fungi extract into the drinking water. Thus, its active compounds might be absorbed more effectively to improve the performance and produce healthy poultry products.